How are prospective science teachers' values and their attitudes toward science associated?: Implications for science teacher training programs - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
This study aimed to examine the associations between prospective science teachers' values (theoretical, religious, economic, aesthetic, social and political values) and their attitudes towards science teaching. Cross-sectional research design was used. The adapted versions of Science Teaching Attitudes Scale (STAS-II) and Allport Vernon Lindzey Values Tests (SOV) were applied to 337 prospective science teachers. STAS-II and SOV were used for assessing prospective science teachers' attitudes toward science teaching and their values respectively. As a result of list-wise deletion, the sample appeared to include 281 prospective science teachers. The data were examined with correlation and stepwise multiple regression analysis. The correlation analysis showed that prospective science teachers' political, social, economic and aesthetic values were not significantly correlated with their attitudes toward science teaching at p<.01 level. On the other hand, prospective science teachers' theoretical values were positively associated with their attitudes toward science teaching (r=0.155, p<.01). Moreover, prospective science teachers' religious values were negatively correlated with their attitudes toward science teaching (r=-0.224, p<.01). Multiple regression analysis also indicated that religious values of prospective science teachers were significant predictors of their attitudes toward science teaching (F (2, 280) = 14.787, p<.01). It can be concluded that there is a weak positive association between prospective science teachers' theoretical values and their attitudes toward science teaching. However, regression analysis reveals that theoretical value is not a significant predictor of attitudes toward science teaching. As for significant predictors of prospective science teachers, it is found that religious values of prospective science teachers are significant predictors, which may negatively affect prospective science teachers' attitudes toward science teaching. So, it is suggested that science teachers must be aware that religion and science are two different ways of knowing. In this respect, the present study emphasizes the importance of explicitly discussing the different ways of knowing in science teacher training programs in order to neutralize the possible negative impacts of religious values of science teachers on their attitudes toward science teaching. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Attitudes toward science teaching; values; prospective science teachers; VIEWS